Taxing Goods and Services in a Digital Era - David R. Agrawal; William F. Fox (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Taxing consumption in the digital economy poses unique challenges for fiscal authorities. Recent institutional reforms, such as states changing remittance rules for the sales and use tax following the Supreme Court decision in South Dakota v. Wayfair, were enacted in order to increase tax revenue collections and create a more neutral tax system. Although these reforms induced more remote vendors to remit taxes on a destination basis, the revenue gains were modest, consistent with most large online vendors remitting taxes prior to the reforms. Instead, following the recent large shock to online shopping from the Covid-19 pandemic, the shift to destination-based taxation has redistributed revenues between large and small local jurisdictions. Increased online shopping raises revenue growth in small jurisdictions while contracting revenues in large jurisdictions. But, Wayfair is not the end of the story: technological changes that induce new consumption patterns, promise new challenges for fiscal authorities. Critical challenges for the next decades include limiting administrative and compliance costs of enforcing taxes in a digital world, determining filing thresholds, dealing with online marketplaces and facilitators, and taxing the consumption of digital services from two-sided platforms. With respect to digital services, we discuss whether consumption taxes should be imposed on both monetized platforms and non-monetized platforms such as social media, and the mechanisms for doing so.
Keywords: H20; H70; K30; L80; R50; 330; sales tax; e-commerce; online shopping; enforcement; compliance; South Dakota v. Wayfair; consumption tax; digital services; platforms